Development of a neutron diffraction system and neutron imaging system for beamport characterization - Unruh, Troy Casey (Kansas State University, 2009)
Semiconductor neutron detector design, fabrication and testing are all performed at Kansas State University (KSU). The most prevalent neutron detectors built by the KSU Semiconductor Materials And Radiological Technologies Laboratory (SMART Lab) are comprised of silicon diodes with [superscript]6LiF as a neutron converter material. Neutron response testing and calibration of the detectors is performed in a neutron detector test facility. The facility utilizes diffraction with a pyrolytic graphite (PG) monochromator to produce a diffracted neutron beam at the northwest beamport of the KSU Training Research Isotope production General Atomics (TRIGA) Mark-II nuclear reactor. A 2-D neutron beam monitor can also be used in conjunction with the test facility for active calibrations. Described in the following work are the design, construction and operation of a neutron detector test facility and a 2-D neutron detection array. The diffracted neutron beam at the detector test facility has been characterized to yield a neutron beam with an average Gaussian energy of 0.0253 eV. The diffracted beam yields a flux of 1.2x10[superscript]4 neutrons/cm[superscript]2/s at 100 kW of reactor power. The PG monochromator is diffracting on the (002) plane that has been positioned at a Bragg angle of 15.5 degrees. The 2-D neutron detection array has been characterized for uniform pixel response and uniform neutron detection efficiency. The 2-D 5x5 array of neutron detectors with a neutron detection efficiency of approximately 0.5 percent has been used as a beam monitor when performing detector testing. The amplifier circuits for the 5x5 array were designed at the KSU Electronics Design Lab (EDL) and were coupled to a LabVIEW field-programmable gate array that is read out by a custom LabVIEW virtual instrument. The virtual instrument has been calibrated to produce a pixel response that varies by less than two percent from pixel to pixel. The array has been used for imaging and active monitoring of the diffracted neutron beam at the detector test facility. The following work is part of on-going research to develop various types of solid state semiconductor neutron detectors.
Keywords: Neutron; Diffraction; Semiconductor; Detector; Silicon; Array; Engineering, Nuclear (0552)